'All our joys will be complated': the visit of George IV to Ireland, 1821. Issue 166 (November 2020) - Holton, Karina
Abstract: The visit of George IV to Ireland in the summer of 1821 prompted an effusive display of royalist emotion. It left a visible and material legacy in Dublin in the form of Kingstown, the Round Room in the Mansion House, King's Bridge, and a variety of prints, paintings, commemorative coins and ephemera. The idea of constructing a palace to facilitate future royal visits was even floated. The visit was reported on extensively in the newspapers of the day and was the subject also of a range of poems, verses and songs. A royal visit made on a whim, together with vested interests and carefully managed propaganda, combined to produce mismatched expectations of what the visit would achieve. This article assesses the visit and argues that while the Dublin administration viewed it as a success, there was, in fact, little positive outcome.